2021
DOI: 10.1038/s41598-021-81930-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of clinically diagnosed RT-PCR swab negative COVID-19: a retrospective cohort study

Abstract: Patients with strong clinical features of COVID-19 with negative real time polymerase chain reaction (RT-PCR) SARS-CoV-2 testing are not currently included in official statistics. The scale, characteristics and clinical relevance of this group are not well described. We performed a retrospective cohort study in two large London hospitals to characterize the demographic, clinical, and hospitalization outcome characteristics of swab-negative clinical COVID-19 patients. We found 1 in 5 patients with a negative sw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…This report found RT-PCR positivity in 67.8% of the SARI patients. This result was similar to previous studies, which reported RT-PCR positivity ranges from 59.2% to 85.8% [10,11]. Di Paolo et al discussed the possibility of positive RT-PCR in repeat testing, which was 4% in their report [19].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This report found RT-PCR positivity in 67.8% of the SARI patients. This result was similar to previous studies, which reported RT-PCR positivity ranges from 59.2% to 85.8% [10,11]. Di Paolo et al discussed the possibility of positive RT-PCR in repeat testing, which was 4% in their report [19].…”
Section: Discussionsupporting
confidence: 90%
“…RT-PCR negative patients had less oxygen requirement (number of days on oxygen) and a better in-hospital survival rate. Middleton et al described a 60% lower probability of death and duration of hospital stay in RT-PCR negative patients [10]. Interestingly, the median duration of illness till admission did not differ between RT-PCR positive and negative groups.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The RT-PCR positive COVID-19 population is well defined. However, owing to low sensitivity of the diagnostic tests including RTPCR, false negativity [ 21 ] is an important problem and “clinically diagnosed RT-PCR negative COVID-19 is now increasingly being recognized [ 22 , 23 ]. In our study we used both RT-PCR positive COVID-19 and clinically diagnosed RT-PCR negative COVID-19 cases.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the study was also not designed nor powered to describe the epidemiology or outcomes of RT-PCR negative COVID. Although we were not able to evaluate the prevalence of RT-PCR negative COVID-19 suspects in our patient population, their considerable prevalence has been suggested previously [ 27 ]. Thirdly, we had limited longitudinal serologic data to determine if some of the earlier seronegative Probables converted to seropositive.…”
Section: Discussionmentioning
confidence: 84%